Sufficient conditions for starlikeness related to a hyperbolic cosine function - Kumar, S. Sivaprasad; Mundalia, Mridula (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5 We determine sufficient conditions for functions to be in the class S^*_ρ formed by starlike functions related to z by using the Briot–Bouquet and other differential subordination techniques. Additionally, in order to ensure the sharpness of our results, we include graphical validations and appropriate illustrations.